Answer:
<u>D</u>
Step-by-step explanation:
The logical step is to <u>factorize the left side of the equation</u>, which becomes:
Then, you can take the square root on both sides.
Not asked, but good to understand the procedure regardless.
Answer:
Step-by-step explanation:
hello :
f(x) = 2x +1 and g(x) = x².
(gºf)(a)= g(f(a)) = g(2a+1) = (2a+1)² = 4a²+4a+1
Answer:
2.061, 2.34, 2.6, 2.601, 2.7
Step-by-step explanation:
Hello!
This is a bit hard to explain! If you want me to try, just comment.
I have arranged the sequence in ascending order below:
.
Hope this helps!